The governance of EU fundamental rights / Mark Dawson. - Dawson, Mark, 1983- (Cambridge studies in European law and policy., 2017)
In spite of a continued increase in the substantive scope and reach of EU fundamental rights, little attention has been paid to their practical enforcement. In this book, Mark Dawson looks at the mechanisms through which EU fundamental rights are protected and enforced, closely examining the interrelation between the EU's pertinent legal and political bodies. He argues that in order to understand EU fundamental rights we must also understand the institutional, political and normative constraints that shape the EU's policies. The book examines the performance of different EU institutions in relation to rights and studies two important policy fields - social rights and rule of law protection - in depth.